A bolha encantada: um estudo sobre mulheres pertencentes à elite econômica paulistana do século XXI - Luconi, Marcella de Castro (2024)
With the aim of covering a historical gap related to women in Brazil, the present work has opted for a still underexplored focus: the subjectivity of women belonging to the economic elite of the city of São Paulo. The choice to study them is situated in time and space. Our objective is to reflect upon their life stories – some of their customs, ideals, and, above all, the commonalities among them in their ways of dealing with wealth and moral values, which allow us to say that they constitute an important social group to be investigated in a plural country like Brazil. The central thematic dimensions of the entire work are: the subjective relationship with marriage, with motherhood, with the city, with the family, with sexual activity, and with the perception of time. The central hypothesis refers to a possible relationship of these women with a closed temporal experience that privileges repetitions of values and customs between generations capable of maintaining the status quo and preserving the distance between rich and poor people already established in the country. Additionally, we suppose that there is a specific "subjective arrangement" of these women to endure these old customs in the 21st century. In an effort to analyze the construction of values of these individuals, it is important to emphasize that this is a study about white, heterosexual, adult women (aged 20 to 70), married, who live on or have a monthly income above 50 times the minimum wage